2011
DOI: 10.1002/acr.20402
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive counseling and use among women with systemic lupus erythematosus: A gap in health care quality?

Abstract: Objectives Disease activity and medication use can complicate pregnancies in SLE. We therefore examined contraceptive counseling and use among women in the University of California, San Francisco Lupus Outcomes Study. Methods In 2008, we queried participants regarding their pregnancy intentions, contraceptive use, and receipt of contraceptive counseling. Premenopausal women <45 years who were sexually active with men were considered at risk of pregnancy. We compared self-reported rates of contraceptive couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 46 publications
4
94
2
4
Order By: Relevance
“…Several conditions may require an effective contraception: early stage of the disease, very active disease, severe organ involvement or damage, use of embryotoxic/fetotoxic drugs. Therefore, contraceptive counselling is essential in the rheumatologic practice, but in the "real life" most women do not receive any information about this issue [110,111]. A common misconception among women with SLE is that they "cannot use birth control", since the "classical" oestrogen-containing pill is generally contraindicated.…”
Section: Contraception Fertility and Assisted Reproductionmentioning
confidence: 96%
“…Several conditions may require an effective contraception: early stage of the disease, very active disease, severe organ involvement or damage, use of embryotoxic/fetotoxic drugs. Therefore, contraceptive counselling is essential in the rheumatologic practice, but in the "real life" most women do not receive any information about this issue [110,111]. A common misconception among women with SLE is that they "cannot use birth control", since the "classical" oestrogen-containing pill is generally contraindicated.…”
Section: Contraception Fertility and Assisted Reproductionmentioning
confidence: 96%
“…(813) Prior studies examining the relationship between chronic conditions and contraceptive use have yielded inconsistent results(1, 1418) and have been limited by their use of cross-sectional, retrospective(14) and self-reported data(14, 16, 17). Some studies focusing on single diseases, such as diabetes mellitus, have reported lower rates of receipt of contraceptive counseling, prescriptions, or services among women with these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the LOS, we found that individuals with SLE received approximately 65% of services recommended in SLE process measures 4. Studies examining osteoporosis prevention and treatment, cardiovascular risk screening, reproductive healthcare, immunisations and also provision of recommended SLE therapies have identified gaps in care for each of these areas 5–7 22 23. Patients who have historically had a higher risk for poor outcomes in SLE, including individuals with low socioeconomic status, were more likely to receive lower quality of care across many of these studies, an effect that seems at least partially mediated by health system characteristics, such as insurance or the systems of care 4.…”
Section: Discussionmentioning
confidence: 99%